2017
DOI: 10.3390/laws6040018
|View full text |Cite
|
Sign up to set email alerts
|

Prioritising Supported Decision-Making: Running on Empty or a Basis for Glacial-To-Steady Progress?

Abstract: Honouring the requirement of the Convention on the Rights of Persons with Disabilities to introduce supported decision-making (SD) has largely been a case of much talk and little real action. As a socio-economic right, actualising support is resource-intensive as well as being fairly uncharted territory in terms of what works, to what degree and for how long benefits last. This paper, drawing lightly on mainly Australian examples, considers unexplored (and sometimes unorthodox) approaches such as the 'needs-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The recognition of decision‐making as a critical component of personhood and citizenship is also important for the realisation of equal rights (Bach & Kerzner, ; Flynn & Arstein‐Kerslake ). As such, Professor Amita Dhandra suggested that “supported decision‐making would be better conceived as a universal component of community life for all citizens, rather than something targeting only those with a disability” (Carney, , p. 49). It is sometimes distinguished from shared decision‐making which has a relatively narrow focus on healthcare professionals working with service users to make healthcare decisions although supported decision‐making does also refer to healthcare decision‐making (Simmons & Gooding, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The recognition of decision‐making as a critical component of personhood and citizenship is also important for the realisation of equal rights (Bach & Kerzner, ; Flynn & Arstein‐Kerslake ). As such, Professor Amita Dhandra suggested that “supported decision‐making would be better conceived as a universal component of community life for all citizens, rather than something targeting only those with a disability” (Carney, , p. 49). It is sometimes distinguished from shared decision‐making which has a relatively narrow focus on healthcare professionals working with service users to make healthcare decisions although supported decision‐making does also refer to healthcare decision‐making (Simmons & Gooding, ).…”
Section: Introductionmentioning
confidence: 99%
“…Carney and Beaupert () argue that implementing supported decision‐making is complicated as it is ‘conceptually ill‐defined’, leaving it open to multiple interpretations. Carney () goes further to suggest that the introduction of supported decision‐making ‘has largely been a case of much talk and little real action’ (p. 18). Shogren and Wehmeyer () have developed a helpful theoretical framework for research and intervention design but, in practice, this work is still developing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Galon and Wineman, 2010, p314) This issue of the quality and context of the moment when mental health social workers and other professionals make such fundamental, potentially life-changing decisions on behalf of the client is now discussed at the interface of mental health and capacity laws the four chosen jurisdictions. Although there will always be situations where substitute decision making is necessary, and appears to be more effective when professional work in these empathic ways, the opportunities to engage in alternative, supportive decision-making process, it is argued, should always be considered, a point made by Carney (2017) in his recent review of the evidence base.…”
Section: Compulsion Substitute and Supported Decision-makingmentioning
confidence: 99%